Research on the bending damage of concrete in areas with large temperature differences based on 3D‐Digital Image Correlation. (24th March 2022) - Shi, Jinna; Zhao, Yanru; Bai, Jianwen; He, Xiaoyan
Abstract: Digital Image Correlation (DIC) technique is used to collect the whole‐field strain of concrete subjected to bending loads under different temperature change cycles, cooling rates, and water‐binder ratio. The bending damage behavior of concrete under large‐difference temperature circulation is analyzed with the whole‐field strain cloud map and data. In addition, with the whole‐field strain obtained by 3D‐DIC technology, the strain‐based damage variable is defined. Furthermore, the damage degree of concrete specimen in the bending process is quantified, and the bending damage evolution process of concrete under the action of temperature circulation is discussed. The results show that the damage of concrete in areas with large temperature differences is related to the number of temperature change cycles as well as the cooling rate. Moreover, the increase in the number of temperature change cycles and the cooling rate will aggravate the bending damage of the concrete. Additionally, the higher the water‐binder ratio, the more serious the adverse effect of temperature circulation on the concrete. This paper provide certain reference for the evaluation of concrete bending deformation damage in areas with a large temperature difference.